Effect of computerized biofeedback relaxation on stress related physiological parameters - Kumar, Mahendra; Srivastava, Priyamvada; Sahu, Manoj K.; Tripathi, Saparya (International Journal Of Community Medicine And Public Health, 2021)
Background: Mental health diseases such as insomnia, anxiety, stress and depression all have a close relationship with the autonomic nervous system. The physiological parameters of autonomic activity viz. galvanic skin resistance, electromyography, respiration and pulse rate can be regulated with the help of computerized biofeedback relaxation training. The main objective of this study was to see the effect of computerized biofeedback relaxation training on psychophysiological parameters of autonomic activity. Methods: In the present study 40 high stress post graduate students were selected. All participants were randomly divided into two group i.e. computerized biofeedback relaxation training (group-1) and placebo group (group-2). Forehead muscle tension, respiration rate, pulse rate and galvanic skin resistance were assessed, and inventories measuring stress were administered pre-randomization. Descriptive, Paired sample ‘t’ test, F-test and Mann-Whitney U test were used to analyze the data with the help of SPSS 16 version. Results: Biofeedback group reported a signiﬁcant change in muscle tension (p=0.27), respiration rate (p=0.01) and galvanic skin response (p=0.35) after relaxation but at the same time control group reported moderate increase in muscle tension. Additionally, the computerized biofeedback group was able to maintain the stress level while the control group had a signiﬁcant increase in the stress level over the 10 days of relaxation training. Conclusions: Biofeedback relaxation useful alternative therapy for management of stress and emotional disturbance in graduate students. During a stressful period this may also be helpful to promote overall psychological health.